Facile synthesis of reduced graphene oxide in supercritical alcohols and its lithium storage capacity - Nursanto, Eduardus Budi; Nugroho, Agung; Hong, Seung-Ah; Kim, Su Jin; Chung, Kyung Yoon; Kim, Jaehoon (ROYAL SOC CHEMISTRY, 2011)
A facile and green method to produce reduced graphene oxide (RGO) nanosheets based on supercritical alcohols is described. The obtained RGO nanosheets exhibited a high carbon-to-oxygen ratio (up to 11.89, determined by X-ray photoelectron spectroscopy), high electronic conductivity (up to 10600 S m(-1)), and high lithium storage capacity with good cyclability (652 mA h g(-1) at a 50 mA g(-1) after 40 cycles) when tested as an anode material.
Keywords: GRAPHITE OXIDE; ION BATTERIES; LI STORAGE; VITAMIN-C; REDUCTION; NANOSHEETS; SHEETS; CARBON; METHANOL; FILMS